The emission band at 5.25 mu m and its relationship to the unidentified emission features at 11-13 and 3.4-3.6 mu m - Roche, P; Lucas, P; Geballe, T (1996)
Spectra at 5-5.6 μm are presented of three planetary nebulae with strong unidentified infrared (UIR) emission bands. All three objects display the 5.25-μm emission band which is attributed to a combination band arising from out-of-plane C-H bending modes. The profiles of the 5.25-μm bands are closely similar to those of the 3.4- and 11.25-μm emission features, confirming that the 5.25-μm feature is a member of the UIR-band family. The origin of this band and its relationship to the UIR bands in the 3.4-3.6 and 11-13 μm spectral regions are discussed. An interpretation of these features in terms of combinations and overtones of the C-H out-of-plane modes is suggested, which, if correct, leads to a simplification of the UIR-band spectrum and suggests that the species that give rise to the bands must have a high degree of symmetry.